Seedling Production of Pak Choy (Brassica rapa L.) using Organic and Inorganic Nutrients - Dody Priadi; Fiqolbi Nuro (Biosaintifika: Journal of Biology & Biology Education, 2017)
Pak Choy or Bok Choy (Brassica rapa L. var. chinensis) is one of favorite Chinese leafy vegetable for various dishes in Indonesia. In this study, it was used as a plant model to identify the appropriate organic hydroponic nutrient solution for leafy vegetable seedling production. The seed was sown on rock wool slabs submerged with 200 ml of a nutrient solution containing biofertilizer of Beyonic StarTmik@Lob (0, 25, 50, 75, and 100%). commercial hydroponic solution (0, 25, 50, 75, and 100%) and its combination (25, 50, and 75%). The experiments were arranged in a CRD. Meanwhile, the obtained data was analyzed using ANOVA followed by DMRT. The relationship among growth parameters was observed using Pearson correlation analysis.  The result of the study showed that the combination of organic and inorganic nutrient (25% Beyonic StarTmik@Lob and 75% commercial hydroponic solution) resulted in the highest seedling growth parameters and leaf indices as well as the perfectly positive correlations among growth parameters. This result indicated that the use of organic nutrient alone was not appropriate for hydroponic seedling production of Pak Choy. Therefore, further study needs to be done to identify the hydroponic solution without inorganic nutrients towards the organic vegetable production.